Composite Stock Price Index during Covid-19 Pandemic at the Indonesian Stock Exchange - Ismawati, Linna (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
COVID-19 pandemic has affected economic conditions, especially markets and industries this year. Covid-19 pandemic resulted in reduced economic growth, decreased investment in the capital market, which was marked by the weakening of the Composite Stock Price Index on the Indonesia Stock Exchange. This study aims to analyze changes in the Composite Stock Price Index in covid-19 pandemic conditions. The research method used is descriptive and verification methods with a quantitative approach. The data used are secondary data including inflation data, Dow Jones Index and Composite Stock Price Index (IHSG), research analysis through multiple regression analysis, classical assumption test, Pearson correlation analysis, coefficient of determination analysis, and hypothesis testing. The results showed that during Covid-19 Pandemic, the Composite Stock Price Index decreased significantly. The relatively high inflation rate and the decline in the Dow Jones Index during Covid-19 pandemic had an impact on the decrease in the Composite Stock Price Index on the Indonesia Stock Exchange. Inflation partially has a significant negative effect on the Composite Stock Price Index (CSPI), while the partial Dow Jones Index has a significant positive effect to the Composite Stock Price Index (CSPI). The results of this study have an impact in determining investment policies for investors and also for making the right decisions by the issuer so as not to cause a decline in stock value.